Respuesta :

For this case we must substitute the values t = 1,2,3 in the given series:

For [tex]t = 1:[/tex]

[tex]4 * (\frac {1} {2}) ^ {t-1} = 4 * (\frac {1} {2}) ^ {1-1} = 4 * (\frac {1} {2})^{0} = 4 * 1 = 4[/tex]

For [tex]t = 2[/tex]:

[tex]4 * (\frac {1} {2}) ^ {t-1} = 4 * (\frac {1} {2})^{2-1} = 4 * (\frac {1} {2})^{1} = 4 * \frac {1} {2} = 2[/tex]

For [tex]t = 3[/tex]:[tex]4 * (\frac {1} {2}) ^ {t-1} = 4 * (\frac {1} {2})^{3-1} = 4 * (\frac {1} {2})^2 = 4 * \frac {1} {4} = 1[/tex]

We add:

[tex]4 + 2 + 1 = 7[/tex]

So, the value is 7.

Answer:

Option C

Answer:

Option C.

Step-by-step explanation:

The given expression is [tex]\sum_{r=1}^{r=3}[4\times (\frac{1}{2})^{(r-1)}][/tex]

We have to find the sum of 3 terms of the sequence formed.

The given sequence is a geometric sequence.

Explicit formula for this sequence is in the form of

[tex]T_{n}=ar^{n-1}[/tex]

In the given formula first term a = 4

and common ratio r = [tex]\frac{1}{2}[/tex]

Sum of a geometric sequence is represented by the expression,

[tex]S_{n}=\frac{a(1-r^{n})}{1-r}[/tex]

[tex]S_{3}=\frac{4(1-\frac{1}{2})^{3}}{(1-\frac{1}{2})}[/tex]

[tex]S_{3}=\frac{4(1-\frac{1}{8})}{(1-\frac{1}{2})}[/tex]

[tex]S_{3}=\frac{4(\frac{7}{8})}{\frac{1}{2} }[/tex]

[tex]S_{3}=7[/tex]

Therefore, Option C is the answer.

ACCESS MORE